Distances between critical points and midpoints of zeros of hyperbolic polynomials - Dimitrov, Dimitar Kolev [UNESP]; Kostov, Vladimir P. (Gauthier-villars/editions Elsevier, 2010)
Let p(x) be a polynomial of degree n with only real zeros x(1) <= x(2) <= ... <= x(n). Consider their midpoints z(k) = (x(k) + x(k+1))/2 and the zeros xi(1) <= xi(2) <= ... <= xi(n-1) of p'(z). Motivated by a question posed by D. Farmer and R. Rhoades, we compare the smallest and largest distances between consecutive xi(k) to the ones between consecutive z(k). The corresponding problem for zeros and critical points of entire functions of order one from the Laguerre-Polya class is also discussed. (C) 2007 Published by Elsevier Masson SAS.
Keywords: Hyperbolic polynomial; Strictly hyperbolic polynomial; Zero; Midpoint; Critical point; Entire function; Laguerre-Polya class